2017
DOI: 10.1097/md.0000000000007682
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of leukoaraiosis from 4683 hospitalized patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 43 publications
(42 reference statements)
7
43
1
Order By: Relevance
“…Of note, all women included in the present study were in menopausal status, therefore, no between-group imbalance in terms of hormonal status can be hypothesized as an underlying confounder. Another hospital-based cross-sectional study observed that female gender was associated with leukoaraiosis even if no quantitative analysis of WMHs was performed [32]. While the biological processes underlying this phenomenon are incompletely understood, it is currently accepted that females have a different susceptibility compared with males to neurodegeneration and neuroinflammatory conditions [33].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all women included in the present study were in menopausal status, therefore, no between-group imbalance in terms of hormonal status can be hypothesized as an underlying confounder. Another hospital-based cross-sectional study observed that female gender was associated with leukoaraiosis even if no quantitative analysis of WMHs was performed [32]. While the biological processes underlying this phenomenon are incompletely understood, it is currently accepted that females have a different susceptibility compared with males to neurodegeneration and neuroinflammatory conditions [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et. al reported both smoking and total HCY levels were shown to be risk factors for LA occurrence (15). Wang et al observed an independent association between Hcy level and severity of the CMBs (16).…”
Section: Discussionmentioning
confidence: 98%
“…Another study found that, in Japanese patients, elevated Hcy level is independently associated with leukoaraiosis, but not with the incidence of microbleeds [15]. Lin et al reported both smoking and total HCY levels were shown to be risk factors for lacunes occurrence [16]. Wang et al observed an independent association between Hcy level and severity of the CMBs [17].…”
Section: Discussionmentioning
confidence: 99%